Co‐creating an Open Government Action Plan: The Case of Sekondi‐Takoradi Metropolitan Assembly, Ghana. (14th December 2017) - Chatwin, Merlin; Arku, Godwin
Abstract: This paper contributes to the limited literature on open government initiatives at the subnational level in developing countries. It examines the motivations of actors in a local government authority to utilize the capabilities of various stakeholders to overcome constraints in cocreating an action plan for open government reforms. This empirical analysis utilized qualitative fieldwork conducted in Sekondi‐Takoradi Metropolitan Assembly, Ghana's third largest local government. The findings demonstrate that a confluence of citizen demand for openness, and willingness within the governance stakeholders, are motivating the pursuit of open government reforms. Viewed through an open innovation framework, we argue that achieving good governance through information transparency, public participation, and accountability reforms is hindered by the institutional environment. Ghana's subnational governments need national level commitment to provide the resources, mandate, and authority to become truly "open."